Peran Aplikasi E-Bekal Dalam Meningkatkan Inovasi Ekonomi Umkm Di Pp Nurul Jadid - Deddy Junaedi; Maziyyatul Husna; Tutut Indrawati; Deva Ummu Azizah; Nur Fajriyah (CV. Akira Java Bulu, 2025)
The study analyzes the role of the E-Bekal application in improving economic innovation of Micro, Small, and Medium Enterprises (MSMEs) at the Nurul Jadid Islamic Boarding School, Probolinggo. This study aims to explore how E-Bekal can improve transaction efficiency, speed up payments, and reduce errors in cash transactions, as well as empower students and MSME actors in facing economic challenges. The methods used in this study are qualitative methods and literature studies. The qualitative approach was carried out through interviews and observations of MSME actors and students. The conclusion of this study is that the E-Bekal system at the Nurul Jadid Islamic Boarding School has a significant role in encouraging economic innovation, especially for Micro, Small, and Medium Enterprises (MSMEs). The implementation of E-Bekal has improved the efficiency of financial transactions, accelerated the payment process, and reduced errors in cash transactions.